Evolution of copro-tests in active detection of colorectal cancer - V. I. Chissov; N. S. Sergeyeva; Ye. V. Zenkina; N. V. Marshrutina (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2012)
The aim of review. To present state-of-the-art in active detection of risk group for colorectal cancer (CRC) by screening laboratory methods – biochemical and immunoenzyme.Key points. The high morbidity and a mortality in the world from CRC makes active detection of this disease very important, thus the first stage of investigation supposes application of non-invasive laboratory methods. It was demonstrated, that biochemical methods for fecal occult blood testing (hemoccult tests) – guaiac Weber's test (gFOBT) and Gregersen test, at adherence to rules of procedure technique, are applicable for active detection of CRC and some other gastro-intestinal diseases. However, low specificity of biochemical tests and necessity of long preparation for analysis limit their clinical application. Searches of the laboratory methods, that allow to overcome this restriction, resulted in development several qualitative (rapid) and quantitative enzyme-linked immunoassays for detection of hemoglobin in feces (FIT). Essential difference of immunoenzyme tests from biochemical is application of antibodies, specific to human hemoglobin and complex of human hemoglobin with haptoglobin. These tests are deprived of some disadvantages of biochemical method. Besides that, detection of the tumor-specific pyruvate kinase type М2 in feces (fTu M2-PK) also can be used in the screening programs for active detection of CRC, as it was shown in series of studies.Conclusion. Now series of copro-tests are available, that are promising for application as screening laboratory methods for active detection of high risk groups for CRC.